The analysis of grammatical structures in written texts of ELF learners - Idaryani Idaryani (ACCENTIA: Journal of English Language and Education, 2022)
This paper aims to analyze the grammatical structures used in the written texts of two English as a foreign language (EFL) learners. One of the EFL learners was from stage 2 and the other was from stage four. Therefore, both learners had different periods in learning English, and also grammatical knowledge of English. The learner in stage 2 has studied English for three terms and the learner in stage 4 has learnt English for two terms. The study was conducted using mixed-method approach. The results of the study showed that writing competence highly relied on the learners’ grammatical structure knowledge in order to express a clear message in writing. The learner of stage 4 was more capable of expressing his message in his writing because of his better ability to use grammatical knowledge in his sentences. The study concludes that the better English grammatical knowledge the learners have, the better expressions can be written by them.